On the N-Solitons Solutions in the Novikov-Veselov Equation - Chang, J.-H. (Symmetry, Integrability and Geometry: Methods and Applications, 2013)
We construct the N-solitons solution in the Novikov-Veselov equation from the extended Moutard transformation and the Pfaffian structure. Also, the corresponding wave functions are obtained explicitly. As a result, the property characterizing the N-solitons wave function is proved using the Pfaffian expansion. This property corresponding to the discrete scattering data for N-solitons solution is obtained in [arXiv:0912.2155] from the ∂¯¯¯-dressing method.